Interactions in Syntrophic Associations of Endospore-Forming, Butyrate-Degrading Bacteria and H(2)-Consuming Bacteria - Tomei, Francisco A. (1985)
Butyrate is an important intermediate in the anaerobic degradation of organic matter. In sulfate-depleted environments butyrate is oxidized to acetate and hydrogen by obligate proton reducers, in syntrophic association with hydrogen-consuming methanogens. This paper describes two enrichments of endospore-forming bacteria degrading butyrate in consortia with methanogens. The isolates are readily established in coculture with H(2)-consuming, sulfate-reducing bacteria by pasteurizing the culture. The two original enrichments differed in that one grew to an optically dense culture while the second grew in clumps. Examination by scanning electron microscopy showed that clumping resulted from the production of large amounts of extracellular polymer. Several H(2)-consuming methanogens were identified in the enrichments. Some of them grew closely associated to the butyrate degraders. This attachment to the hydrogen producer may permit some methanogens to compete for the growth substrate against other bacteria having higher substrate affinity.